2010
DOI: 10.1039/c0sc00280a
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in oxyallyl–furan (4 + 3) cycloadditions: control of intermediate conformations and dispersive stabilisation in cycloadditions involving oxazolidinone auxiliaries

Abstract: Chiral oxazolidinones were previously thought to control cycloaddition stereoselectivity by steric crowding of one face of the substrate. We have discovered that in 4+3 cycloaddition reactions of oxallyls, the stereoinduction is caused instead by stabilising CH–π interactions that lead to reaction at the more crowded face of the oxazolidinone. Density functional theory calculations on the 4+3 cycloadditions of oxazolidinone-substituted oxyallyls with furans establish unexpected transition state conformations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…Consequently, Krenske, Houk, and Hsung 143 conducted a detailed mechanistic study of this nitrogenstabilized oxyallyl cation [4 + 3] cycloadditions to provide a rationale. DFT calculations revealed that the E -oxyallyl cations were actually the preferred species regardless of the presence of ZnCl 2 , and there was no bidentate coordination (Scheme 149).…”
Section: Reactions Of Allenamidesmentioning
confidence: 99%
“…Consequently, Krenske, Houk, and Hsung 143 conducted a detailed mechanistic study of this nitrogenstabilized oxyallyl cation [4 + 3] cycloadditions to provide a rationale. DFT calculations revealed that the E -oxyallyl cations were actually the preferred species regardless of the presence of ZnCl 2 , and there was no bidentate coordination (Scheme 149).…”
Section: Reactions Of Allenamidesmentioning
confidence: 99%
“…[13] The phenyl-substituted furfuryl alcohol 7 (see Table 1, entry 5) was chosen for this purpose, as this substrate gives mostly exo-selective cycloaddition. Several competing pathways have been investigated in an effort to deduce a plausible mechanism (Scheme 3).…”
mentioning
confidence: 99%
“…[11] We also computed the NICS values at the (3, + 1) ring critical point of the electron density to prove the aromaticity of TS a. Given the unsymmetrical character of our cyclic systems, we needed to define the inner points unambiguously.…”
Section: Resultsmentioning
confidence: 99%